Silicone rubber nanocomposites: optimal graphene dosing for mechanical and electrical enhancements - Vishal, Deore; Milinda, Mahajan; I., Siva; Avinash, Shinde; Smita, Waghmare; Sharul, Sham Dol; K.A., Ahmad; Mohamed Thariq, Hameed Sultan (Elsevier, 2024)
The combination of lightweight, durable, and flexible elastomer nanocomposites presents a unique set of features that make them highly promising for a range of several engineering applications. Present work investigates the performance of the mechanical and electrical characteristics of a nanocomposite produced by combining silicon rubber (SR) with nano-Graphene, copper oxide (CuO). Two roll mixing followed by compression moulding is used to manufacture different configurations of Graphene/CuO/SR nano composite. Nano composites specimens are fabricated with 1, 2, 4, and 8 wt % of graphene with fixed 1 % CuO. There has been a discernible improvement of 146.52 % in the mechanical properties and 18.1 % in electrical performance. This improvement is supported by the FESEM morphological analysis of fractured surfaces. It has been observed that the optimized loading of 8 wt % of Graphene gives the best performance. The strong interfacial interaction between the Graphene/CuO and SR is responsible for the performance gain.